Geometrically Nonlinear Finite Element Formulation for Marine Risers - JIE, KOH KIM (2018)
This thesis presents a large displacement, small strain formulation for the analysis of flexible marine risers and addresses present computational shortcomings associated with hydrostatic and hydrodynamic forces in the geometrically nonlinear setting. The continuum mechanics incremental equation of motion, which essentially stems from the Newton–Raphson method, serves as the basis for the nonlinear formulation.